THE IMPLEMENTATION OF A QUALITY MANAGEMENT SYSTEM IN A BUILDING OF A COMPETITIVE ADVANTAGE BY MEDICAL ENTITIES - Czerw, Aleksandra; Religioni, Urszula (Ekonomia i Prawo. Economics and Law, 2013)
The growing requirements of patients in relation to the quality of health services, as well as the existing competition in the health services market, force medical entities to constant process improvement. For this purpose, medical institutions appoint professionals responsible for the planning and development of quality policy strategy, which aims at maintenance or obtainment of the current market standards. The aim of this article is to show the role of the quality management system in the functioning of medical entities. For that purpose, the authors characterized the ISO standard, which is the basis for the creation of quality management systems, presented the stages of the quality management implementation, and pointed out the benefits associated with the introduction of the quality management idea in medical entities.